Type Six Secretion System of Bordetella bronchiseptica and Adaptive Immune Components Limit Intracellular Survival During Infection - Bendor, Liron (2015)
The Type Six Secretion System (T6SS) is required for Bordetella bronchiseptica cytotoxicity, cytokine modulation, infection, and persistence. However, one-third of recently sequenced Bordetella bronchiseptica strains of the predominantly human-associated Complex IV have lost their T6SS through gene deletion or degradation. Since most human B. bronchiseptica infections occur in immunocompromised patients, we determine here whether loss of Type Six Secretion is beneficial to B. bronchiseptica during infection of immunocompromised mice. Infection of mice lacking adaptive immunity (Rag1-/- mice) with a T6SS-deficient mutant results in a hypervirulent phenotype that is characterized by high numbers of intracellular bacteria in systemic organs. In contrast, wild-type B. bronchiseptica kill their eukaryotic cellular hosts via a T6SS-dependent mechanism that prevents survival in systemic organs. High numbers of intracellular bacteria recovered from immunodeficient mice but only low numbers from wild-type mice demonstrates that B. bronchiseptica survival in an intracellular niche is limited by B and T cell responses. Understanding the nature of intracellular survival during infection, and its effects on the generation and function of the host immune response, are important to contain and control the spread of Bordetella-caused disease.